CORRODED GAS PIPELINE REMAINING LIFE UNDER VARIABLE OPERATING PRESSURE - Belkacemi, M.H.; Benzerga, D.; Choutier, A.; Haddi, A. (Journal of Mechanical Engineering and Technology (JMET), 2023)
Gas pipelines are subjected to mechanical and chemical stresses which lead to failures of various types such as corrosion, cracking, deformation and rupture. Corrosion damage to pipelines has become a growing concern in the gas industry. Corrosion defects in the form of pitting caused by the corrosion phenomenon cause high concentrations of stresses and plastic strains thus reducing the strength of the pipe by threatening its structural integrity. Indeed, the internal operating pressure is variable and can generate the phenomenon of fatigue, which is dangerous, given its insidious nature, causing damage to the corroded zone for stress levels well below the yield stress of the material. The standards used in the framework of the rehabilitation of corroded pipes allow the determination of their burst pressure but not their remaining life. To address this issue, we have developed a model based on damage mechanics to predict the remaining life of a pipe in the presence of an external corrosion defect